Sistem Pendukung Keputusan Menentukan Penerima Program Bantuan Sosial Menggunakan Metode Analytical Hierarchy Process (AHP) - Vicky Rahmawan; Heri Haerudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In determining the potential recipients of social assistance in the Sukalaksana Village, the distribution of assistance to the community is still not on target and many poor people do not receive social assistance because the program assistance is not yet effective. With so many residents having different criteria from various aspects of life, it will be difficult for RT/RW officials to determine which residents should be more deserving of social assistance. And also there is still invalid data on recipients of social assistance for residents who have died and moved their domicile but are still recorded as receiving social assistance.Therefore the authors designed a Decision Support System Application to determine beneficiaries of the Social Assistance Program based on the method used. Namely by utilizing the Analytical Hierarchy Process (AHP) method. One of the methods in the AHP method is that there are several calculation processes that are used as data references and pairwise comparisons to explain evaluation factors and weighting factors in multi-factor conditions in the selection of recipients of social assistance. So that it will be very helpful and facilitate RT / RW officers in assessing residents who are eligible to receive social assistance.